Descriptors for Baobab (Adansonia digitata L.) Kehlenbeck K.S. Padulosi, A. Alercia Bioversity International, World Agroforestry Centre Italy, Kenya, 2015 - Van Damme, Patrick (Afrika Focus, 2015)
Bioversity International belongs to the so-called CG centre group. The latter, in full the Consultative Group on International Agricultural Research (though no longer known under their full name), consists of some fteen research centres that are members of the CGIAR Consortium. Each centre has a global mandate to study, improve and promote (sub)tropical crops and animal production. Research is carried out in close collaboration with hundreds of partners, including national and regional research institutes, civil soci- ety organizations, academia, development organizations and the private sector.